Det skotske Agerbrug ved Tangaagaard. (Fortsat) Fra 1ste August 1855 til 1ste August 1856. - Sehested, F. (Tidsskrift for Landøkonomi, 2018)
Det skotske Agerbrug ved Tangaagaard. (Fortsat) Fra 1ste August 1855 til 1ste August 1856.